The conception of an argument by analogy and examples of its application in the jurisprudence of administrative courts - Kowalewski, Kamil Piotr (The Opole Studies in Administration and Law, 2017)
This article attempts to analyze the construction and application of the per analogiam argument in a practical legal discourse. The author seeks to examine, how the per analogiam argument is constructed, and how is it used by participants of a practical legal discourse. With the aim to find an answer to these questions the author analyzes a number of the judgments passed by the Supreme Administrative Court, wherein the Court comments on how to use the argument of similarities correctly. In addition, the author summarizes the deliberations of the Court on the arguments of similarities with the views of the doctrine on this issue. All these procedures make it possible to determine how and when we should use the per analogiam argumentation to achieve the desired results.